The Effect of Albendazole Administration and Iron-Folic Acid Supplementation on Hemoglobin Level in Primary Schoolchildren with Soil-transmitted Helminth Infections - Wijaya, Willhans; Pasaribu, Ayodhia Pitaloka; Suteno, Erwin; Husin, Nirmala; Pasaribu, Syahril (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Soil-transmitted helminth (STH) infections were the highest infection in children aged 5–15 years old. They lead to iron deficiency anemia and folic acid deficiency. One of the strategies to treat the issues is anthelmintic administration with iron-folic acid supplementation. AIM: This study aims to evaluate the effectiveness of single-dose albendazole and albendazole with iron-folic acid supplementation on hemoglobin (Hb) levels in children with STHs. METHODS: This was an open-label randomized clinical trial conducted in Batubara Regency from September to November 2018. Subjects were primary schoolchildren with STH infections. They were grouped into albendazole and albendazole with iron-folic acid supplementation groups. The data were analyzed by independent t-test and Mann–Whitney U-test. RESULTS: From 139 children, 72 children received albendazole single dose and 67 children received albendazole with 30 mg iron and 250 μg folic acid weekly for 3 months. The median of baseline hemoglobin level was 12.2 gr/dL, whereas after intervention was 12.7 gr/dL. The hemoglobin level increases did not differ significantly between the two groups (p > 0.05). However, clinical improvement was observed. CONCLUSION: Iron-folic acid supplementation in addition to albendazole did not show any benefit for primary schoolchildren with STH infection in Batubara Regency, North Sumatera, Indonesia.